2021
DOI: 10.1016/j.cell.2021.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Transmission, infectivity, and neutralization of a spike L452R SARS-CoV-2 variant

Abstract: We identified an emerging SARS-CoV-2 variant by viral whole-genome sequencing of 2,172 nasal/nasopharyngeal swab samples from 44 counties in California, a state in the Western United States. Named B.1.427/B.1.429 to denote its 2 lineages, the variant emerged in May 2020 and increased from 0% to >50% of sequenced cases from September 2020 to January 2021, showing 18.6-24% increased transmissibility relative to wild-type circulating strains. The variant carries 3 mutations in the spike protein, including an L452… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
354
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 488 publications
(391 citation statements)
references
References 65 publications
11
354
1
Order By: Relevance
“…Of the 63 publications included, five were non-peer reviewed preprints [16,17,52,54,66]. Eleven articles reported in vitro, in silico or animal model studies [15,18,19,[22][23][24][25][26][27][28][29]; nineteen articles reported clinical studies [16,[37][38][39][41][42][43][44][45][46][47][48][49]51,[70][71][72][73]. The remaining 33 articles analyzed SARS-CoV-2 genomes downloaded from the GISAID or other available databases with patient status [8][9][10][11]20,21,[30][31][32][33][34][35][36]40,50,…”
Section: Study Selection and Types Of Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 63 publications included, five were non-peer reviewed preprints [16,17,52,54,66]. Eleven articles reported in vitro, in silico or animal model studies [15,18,19,[22][23][24][25][26][27][28][29]; nineteen articles reported clinical studies [16,[37][38][39][41][42][43][44][45][46][47][48][49]51,[70][71][72][73]. The remaining 33 articles analyzed SARS-CoV-2 genomes downloaded from the GISAID or other available databases with patient status [8][9][10][11]20,21,[30][31][32][33][34][35][36]40,50,…”
Section: Study Selection and Types Of Studiesmentioning
confidence: 99%
“…Twenty-five studies reported the relation between viral mutations and virus load or infectivity of SARS-CoV-2 (Table 2), of which five articles (two in vitro/animal model studies [18,19], two studies based on SARS-CoV-2 genomes downloaded from electronic databases or community-based testing datasets (bigdata analysis) [20,21] and one clinical study [16]) showed no impact of mutations with infectivity of SARS-CoV-2. The remaining 20 studies (nine in vitro/animal model or in silico studies [15,[22][23][24][25][26][27][28][29], eight bigdata analyses [9,[30][31][32][33][34][35][36] and three clinical studies [37][38][39]) showed that SARS-CoV-2 variants were significantly associated with increase in infectivity. All studies performed on the variants of concern (VOCs) have linked these mutations to increased viral transmissibility [23,[27][28][29][34][35][36]38,39], except for one study by Li et al [19].…”
Section: Relation Between Viral Mutation and Infectivity Of Sars-cov-2mentioning
confidence: 99%
“…We also identified seven patients with COVID-19 caused by B.1.617.1 or B.1.617.2, variants reported to be causing widespread disease and extensive public health concern in India. [43][44][45][46][47][48] In the aggregate, our genome data show that VOC and VOI now account for the great majority of all new COVID-19 cases in our region.…”
Section: [Introduction]mentioning
confidence: 65%
“…Serially diluted samples were then added to 96-well plates, mixed with pseudotyped virus, and incubated at 37°C for 1 hour. Thereafter, 2×10 4 Huh-7 cells/100 μL were added to each well of the 96-well plate. Cells were then incubated at 37°C with 5% CO2.…”
Section: Methodsmentioning
confidence: 99%